The text and its illustrations. Intersemiotic and intercultural dialogues : the cases of Persiles and Quixote in Europe and Africa (20th-21st centuries) - (:unkn) unknown (My University, 2021)
This doctoral thesis studies the inter-semiotic (text/image), intercultural (Europe/Africa) and transhistorical (17th, 20th and 21st centuries) dialogues between Persiles (1617), the Quixote (1610-1615) and their modern and post-modern iconographic rewritings (1947, 2016 and 2017).These travels enable analysing different ways of thinking and, above all, on the one hand, how the Baroque artistic-literary modus operandi was contemporised and, on the other hand, what means are used to carry out the processes of Africanised reterritorialisation of a way of thinking that turn out to be basically Hispanic.In primis, it is shown that the hypotext of the Persiles is in tune with the dynamics of the Baroque, since it is motivated by an abundant flow of scriptural images that are an imitatio-conformatio of the emblematic literature real emblems or, reveal themselves as mere creatio of Miguel de Cervantes.Secondly, and in relation with the problematic that features the Persiles, the Quixote and their postmodern illustrations, it can be established that the two semiotic territories (texts/images) are in constant dialogue under the lens of the joint relations (shared aesthetic and socio-cultural codes). However, the illustrators also mark a departure from hypotexts by creating a pictorial grammar that is either mixed and cubanised (as in the case of the painter Echenique) or Africanised (as in the case of the DQRN series). Finally, the study of the Quixote according to the archetypal and mythographic approaches enables to reveal its transcendental and transcultural aspect, which has made it possible to approach the socio-cultural character of the Quixote myth from its humanism and values which are aesthetically embodied in African rewritings. Indeed, while Persiles is imbued with Western socio-cultural codes, the Quixote, in contrast, enables a more universal scope that joins and includes the codes of African representation.
Keywords: African Research